Understanding the strengthening effect of curdlan on the quality of frozen cooked noodles: studies on water characteristics and migration during cooking. (27th June 2022) - Liu, Hao; Liang, Ying; Guo, Shibo; Liu, Mei; Chen, Zilu; He, Baoshan; Zhang, Xia; Wang, Jinshui
Summary: This study aimed to further clarify the influence of curdlan on the quality of frozen cooked noodles (FCN) by exploring the changes in the microstructure, rheological properties and water status of FCN during cooking. The addition of curdlan delayed the disappearance of the white core in FCN during cooking. Compared with FCN without curdlan, the microstructure of FCN with curdlan was more homogeneous, and 0.5% curdlan showed the best improvement. Furthermore, higher G′ and G′′ values and lower strain values were measured in the presence of 0.5% curdlan. Throughout the cooking process, the freezable water content significantly increased. Combined with the result of water distribution, it can be inferred that the reduction of freezable water content induced by curdlan was occurred by changing the status of water. Moreover, the result of magnetic resonance imaging indicated that the water migration rate decreased after the addition of curdlan. The results demonstrate that curdlan mitigates the degradation of FCN structure during cooking by limiting the mobility of water, which also provides new insights for improving the quality of FCN and the application of curdlan. Abstract : The thermally irreversible gel formed by curdlan during the cooking of frozen cooked noodles has a positive effect on the microstructure, rheological properties and other qualities of frozen cooked noodles after cooking.